التجربة الجزائرية في مواجهة الجريمة الإرهابية - دحية، عبداللطيف (جامعة الجزائر1 بن يوسف بن خدة, 2017)
This study aims to shed light on the major efforts made by Algeria in the fight against terrorist crime, and was divided into two parts, in the first part, we talked about the confrontation of the legislative terrorist crime through speaking about different laws that have talked about the fight against terrorist crime, as well as laws that have been adopted to promote peace and reconciliation. In the second part of this study we discussed about the institutional confrontation of terrorist crime through speaking about the role of civil institutions in the confrontation of terrorist crime, and the role of the military and paramilitary institutions in combating this criminal model ,in conclusion we present the results and recommendations offered
تهدف هذه الدراسة إلى إلقاء الضوء على أهم الجهود التي اتخذتها الجزائر في مواجهة الجريمة الإرهابية، وقد قسمناها إلى جزئيين، في الجزء الأول تحدثنا عن المواجهة التشريعية للجريمة الإرهابية من خلال الحديث عن مختلف القوانين التي تحدثت عن مكافحة الجريمة الإرهابية وكذا التشريعات التي تم سنها لتشجيع السلم والمصالحة. أما الجزء الثاني من هذه الدراسة فتم التطرق فيه للمواجهة المؤسساتية للجريمة الإرهابية من خلال الحديث عن دور المؤسسات المدنية في مواجهة الجريمة الإرهابية وكذا دور المؤسسات العسكرية وشبه العسكرية في مواجهة هذا النمط الإجرامي، كما ختمنا دراستنا هذه بخاتمة تضمنت بعض النتائج والتوصيات.
Keywords: قوانين وتشريعات -- الجريمة الإرهابية -- الجزائر -- الإرهاب